Determinan Stunting pada Balita Usia 12-59 Bulan di Puskesmas Bojongsari Kota Depok - Ayu Wulansari; Astrid Novita; Herjanti (SIMFISIS Jurnal Kebidanan Indonesia, 2021)
Introduction: Specifically for the 12-24 month age group, the report on the results of weighing children under five at the sub-district level in Depok City shows that the Depok sub-district is the sub-district that has the highest prevalence of stunting (22.3%). Objectives: This study aims to determine whether there is a relationship between birth weight, exclusive breastfeeding, immunization status, and infant and child feeding on the incidence of stunting in toddlers at the Bojongsari Health Center in 2021. Method: Respondents in this study were mothers who had stunted toddlers aged 12-59 months who were located in the Bojongsari Health Center area. This research is quantitative research with the analytic method with a cross-sectional approach. The population taken by toddlers who experienced stunting amounted to 130 respondents and the number of samples was 97 respondents. The sampling technique used was the Lemeshow formula with purposive sampling. The types of data used are secondary and primary data with univariate and bivariate analysis. The data were processed using SPSS 25. Result: The results of the Chi-square statistical test for birth weight variables (p-value = 0.027), exclusive breastfeeding (p-value = 0.038), immunization status (p-value = 0.036) and infant feeding and child (p-value=0.000). Conclusion: There is a relationship between birth weight, exclusive breastfeeding, immunization status, and infant and child feeding on the incidence of stunting in toddlers aged 12-59 months at the Bojongsari Health Center, Depok City in 2021.